Miners landing their supplies on the beach at Teller, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Miners landing at Teller, Alaska" Original image in Hegg Album 31, page 9. Original photograph by Eric A. Hegg 1255; copied by Webster and Stevens 174.A. Nome Gold Rush.